A review of the challenges, learnings and future directions of home handheld spirometry in interstitial lung disease - Maher, Toby M.; Schiffman, Courtney; Kreuter, Michael; Moor, Catharina C.; Nathan, Steven D.; Axmann, Judit; Belloni, Paula; Bengus, Monica; Gilberg, Frank; Kirchgaessler, Klaus-Uwe; Wijsenbeek, Marlies S. (Respiratory research, 2022)
Patients with interstitial lung disease (ILD) require regular physician visits and referral to specialist ILD clinics. Difficulties or delays in accessing care can limit opportunities to monitor disease trajectory and response to treatment, and the COVID-19 pandemic has added to these challenges. Therefore, home monitoring technologies, such as home handheld spirometry, have gained increased attention as they may help to improve access to care for patients with ILD. However, while several studies have shown that home handheld spirometry in ILD is acceptable for most patients, data from clinical trials are not sufficiently robust to support its use as a primary endpoint. This review discusses the challenges that were encountered with handheld spirometry across three recent ILD studies, which included home spirometry as a primary endpoint, and highlights where further optimisation and research into home handheld spirometry in ILD is required.